Implementation of Social Forestry in Nagari Gunung Selasih, Dharmasraya Regency, West Sumatra Province - Assahab, Achmal; Elvawati; Zulfa (PT Inovasi Pratama Internasional, 2026)
Indonesia’s social forestry policy aims to reconcile forest conservation with community welfare through legal access and community-based forest management. This article analyses the implementation of the Minister of Environment and Forestry Regulation (Permen LHK) No. 9/2021 on Social Forestry in Nagari Gunung Selasih, Dharmasraya District, West Sumatra. This study focuses on the roles of key actors, the implementation of social forestry schemes, their contributions to local livelihoods, and the main constraints faced. Using a qualitative descriptive design within a constructivist paradigm, data were collected through document analysis and in-depth interviews with government officials, social forestry group leaders, and community members, as well as non-participant observations of four Social Forestry Business Groups (Kelompok Usaha Perhutanan Sosial): KUPS Kopi Sungai Lomak, KUPS Randang Paku Rangkito, KUPS Trigona Gunung Selasih, and KUPS Ekowisata Ngalau Sungai Suko. The findings show that the Forest Management Unit (KPHP) acts as a facilitator, regulator, and technical advisor, whereas KUPS operationalize livelihood diversification through non-timber forest products and environmental services. Social forestry generates supplementary income, strengthens local institutions, and reinforces cultural values but is constrained by limited capacity, capital, infrastructure, and latent conflicts. This article argues that sustained multi-actor collaboration is essential for transforming legal access into durable socio-ecological benefits.